Pengaruh Fear Of Missing Out (FOMO) Terhadap Harmonious Brand Passion dan Obsessive Brand Passion Serta Dampaknya Terhadap Brand Addiction Pada Konsumen Skincare di Media Sosial - Fina Puspita Laut; Ritta Setiyati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of Fear of Missing Out (FOMO) on harmonious brand passion (HBP) and obsessive brand passion (OBP), as well as the impact of obsessive brand passion on brand addiction among skincare consumers on social media. The increasing phenomenon of FOMO, driven by the intensity of social media usage, encourages consumers to follow trends, particularly in skincare products associated with lifestyle and self-image. This study employs a quantitative approach using a survey method involving 150 respondents who are active social media users and have purchased skincare products. The sampling technique used is purposive sampling, and the data are analyzed using linear regression with SPSS. The results show that FOMO has a positive and significant effect on both HBP and OBP. In addition, OBP also has a positive and significant effect on brand addiction. These findings indicate that higher levels of FOMO lead to stronger emotional attachment to brands, both harmoniously and obsessively, which ultimately increases the tendency toward addictive consumption behavior. This study implies that social media-based marketing strategies should be implemented carefully to avoid encouraging excessive consumer behavior.